The role of Lon-mediated proteolysis in the dynamics of mitochondrial nucleic acid-protein complexes - Nina Kunová (Nature Portfolio, 2017)
Abstract Mitochondrial nucleoids consist of several different groups of proteins, many of which are involved in essential cellular processes such as the replication, repair and transcription of the mitochondrial genome. The eukaryotic, ATP-dependent protease Lon is found within the central nucleoid region, though little is presently known about its role there. Aside from its association with mitochondrial nucleoids, human Lon also specifically interacts with RNA. Recently, Lon was shown to regulate TFAM, the most abundant mtDNA structural factor in human mitochondria. To determine whether Lon also regulates other mitochondrial nucleoid- or ribosome-associated proteins, we examined the in vitro digestion profiles of the Saccharomyces cerevisiae TFAM functional homologue Abf2, the yeast mtDNA maintenance protein Mgm101, and two human mitochondrial proteins, Twinkle helicase and the large ribosomal subunit protein MrpL32. Degradation of Mgm101 was also verified in vivo in yeast mitochondria. These experiments revealed that all four proteins are actively degraded by Lon, but that three of them are protected from it when bound to a nucleic acid; the Twinkle helicase is not. Such a regulatory mechanism might facilitate dynamic changes to the mitochondrial nucleoid, which are crucial for conducting mitochondrial functions and maintaining mitochondrial homeostasis.